Chemistry tutoring sessions: educational support program for health sciences students. - Layton-Jaramillo, Soraya Elena; Moncada, Ligia (Revista Facultad de Medicina de la Universidad Nacional de Colombia)
Introduction: A high proportion of health sciences students at the Universidad Nacional de Colombia (UNAL) fail the basic chemistry (BC) course and, in some cases, this situation has caused them to lose their status as UNAL students. Objective: To evaluate the efficacy of a tutoring program in reducing the percentage of health sciences students who fail the BC course at the UNAL. Materials and methods: Holistic research carried out between 2011 and 2018, consisting of four levels and involving the participation of professors and students of the BC course, as well as professors and directors of the health sciences programs offered by the UNAL. At the perceptual level, the problem was described through the quantitative analysis of the academic reports of 1 983 students enrolled in the course from 2009 to 2011. At the apprehensive level, semi-structured interviews were conducted with 5 directors and 8 professors of the different health sciences programs, and a questionnaire was administered to 319 students to analyze the causes and possible solutions to the problem. At the comprehensive level, a tutoring program (designed according to the context-based learning approach), in which 3 050 students participated, was implemented. Finally, at the integrative level, the efficacy of the program was evaluated by comparing, through bivariate analyses, the academic results obtained in the BC course by the 4 545 students enrolled between 2011 and 2018 based on to their participation in the tutoring program. Results: A significant difference in the course failure rate (p=0.000) was observed between students who participated in the tutoring program (18.73%) and those who did not (43.26%). Conclusion: The implementation of the chemistry tutoring program allowed to reduce the failure rate of the BC course among health sciences students at the UNAL.